1991
DOI: 10.1007/bf00555720
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging versatile thinking in algebra using the computer

Abstract: In this article we formulate and analyse some of the obstacles to understanding the notion of a variable, and the use and meaning of algebraic notation, and report empirical evidence to support the hypothesis that an approach using the computer will be more successful in overcoming these obstacles. The computer approach is formulated within a wider framework of versatile thinking in which global, holistic processing complements local, sequential processing. This is done through a combination of programming in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
4

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 5 publications
1
31
0
4
Order By: Relevance
“…(Gray & Tall, 1994) This notion of procept proved to be present throughout a large portion of mathematics. Tall & Thomas (1991) had already noted that, for many children, an expression such as 2 + 3x may be conceived as a process which cannot be carried out until the value of x is not known -a reinterpretation of the notion of "lack of closure" discussed by earlier authors. Gray and Tall (1994) also noted the peculiar case of the limit concept where the (potentially infinite) process of computing a limit may not have a finite algorithm at all.…”
Section: Theories Of Encapsulation/reificationmentioning
confidence: 99%
See 2 more Smart Citations
“…(Gray & Tall, 1994) This notion of procept proved to be present throughout a large portion of mathematics. Tall & Thomas (1991) had already noted that, for many children, an expression such as 2 + 3x may be conceived as a process which cannot be carried out until the value of x is not known -a reinterpretation of the notion of "lack of closure" discussed by earlier authors. Gray and Tall (1994) also noted the peculiar case of the limit concept where the (potentially infinite) process of computing a limit may not have a finite algorithm at all.…”
Section: Theories Of Encapsulation/reificationmentioning
confidence: 99%
“…Focusing on both operational processes and the properties of objects-either in turn or at the same time-gives a versatile approach (Tall & Thomas, 1991). This proves particular valuable when computer software is available to carry out the processes internally, allowing the individual to focus either on the study of the processes, which they may carry out, or program, for themselves, or on the concepts produced by the computer (Tall & Thomas, 1989).…”
Section: The Scope Of the Process-object Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…However other research can also be re-interpreted in proceptual terms. We have evidence that the lack of formation of the procept for an algebraic expression causes difficulties for pupils who see the symbolism representing only a general procedure for computation: an expression such as 2+3x may be conceived as a process which cannot be carried out because the value of x is not known (Tall & Thomas, 1991). We have evidence that the conception of a trigonometric ratio only as a process of calculation (opposite over hypotenuse) and not a flexible procept causes difficulties in trigonometry (Blackett 1990, Blackett & Tall 1991.…”
Section: Examples From Other Areas Of Mathematicsmentioning
confidence: 99%
“…The influential Cockcroft report in the UK (DES 1982, p. 60) indicated that "algebra is a source of considerable confusion and negative attitudes among pupils" and as teachers we want to make sure that "algebra is not a meaningless game with 26 letters" (Freudenthal 1973, p.290, his emphasis). The difficulties include how the equals sign is viewed (Kieran 1981), the meaning given to letters (Küchemann 1981), the reading of formal mathematical notation (Kirshner 1989) and the need to treat an algebraic expression as an object as well as a process (Booth 1984;Tall and Thomas 1991).…”
Section: Introductionmentioning
confidence: 99%